Penguatan profil pelajar pancasila melalui self-regulated learning (SRL) pada siswa sekolah luar biasa (SLB) - Rahmawati, Eni Eni; Wardhani, Novia Wahyu; Kristiono, Natal Natal; Azzikra, Avatar Amer; Insani, Hanifah Nur; Rahayu, Slamet Sugi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Education plays an important role in shaping the character and personality of individuals and society, so that it becomes one of the determinants of national progress. The Minister of Education and Culture Regulation stipulates that currently one of the focuses of education in Indonesia is developing a student profile based on Pancasila values. The Pancasila Student Profile is an innovative step in improving the quality of education, especially student character. This study aims to determine the application of self-regulated learning to strengthen the Pancasila student profile at Special Schools (SLB) C in Central Java. This study uses a qualitative method with a case study approach. The results of the study indicate that in this study, Self-Regulated Learning refers to the abilities of students at SLB C shown through three phases, namely the planning phase (forethought phase), the performance control phase (performance control phase), and the self-reflection phase (self reflection phase). The planning phase is constrained because students do not yet have the independence to prepare a study plan to achieve their goals. The work control phase is difficult to do because students have difficulty concentrating to achieve learning goals, are not yet able to manage their own study time, and measure their learning success independently. The self-reflection phase is still difficult to do because students have difficulty in evaluating their own learning performance and do not yet have the initiative to achieve learning goals.